Optical response of hollow gold nanoparticles - Illyashenko, L. N.; Stognii, N. P.; Nerukh, O. G. (My University, 2019)
The work is aimed at understanding relations between the sensitivity of nanoparticle to the size of internal surface of the hollow Au nanoparticles, which can provide guidelines for a choice of their parameters to be used for new applications in biological sensing and imaging, medical diagnostics, drug development, photo-thermal therapy of cancer and bacterial infection.
Keywords: nanoparticles; scattering cross-section